GAMBARAN PERSEPSI SUAMI TENTANG EFEK SAMPING KONTRASEPSI KB SUNTIK PADA ISTRI - Debby Saputri; Yulia Irvani Dewi; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Family planning (FP) is an act that helps couples to regulate birth spacing, and determine the number of children in thefamily. Injecting family planning users will experience physiological changes. he use of injecting FP will have animpact on the acceptors. One of the side effects of injecting FP is perceived as a physiological change such as weight,irregular menstruation, and others. These changes are also felt by the husband. The aim of this research wasto determine the description of the husband's perception of the contraceptive side effects of contraception injecting thewife. The research design used was a simple descriptive with a total sample of 35 people. The sampling technique usedcluster sampling technique conducted by randomization. Data collection tool used is questionnaire. The analysis used isunivariate analysis to see the frequency distribution. The results showed that most of the respondents had positiveperception about KB side effect on wife (54,3%). Based on research results, it is suggested for health services to keepreturning to provide education about contraception, and side effects.Keywords: Husband’s perception, Side Effects Of Injectable Contraception.